Affective trust in buyer-seller relationships: a two-dimensional scale. Issue 2 (7th March 2016) - Akrout, Houcine; Diallo, Mbaye Fall; Akrout, Wafa; Chandon, Jean-Louis
Abstract : Purpose: – This paper aims to develop and validate a scale measurement of trust in long-term relations, specifically in the maintenance phase, between buyers and sellers. Relying on a cognitive conception, existing scales do not measure the affective trust occurring in the maintenance stage of the relationship. Design/methodology/approach: – Three surveys were conducted with purchasing managers of enterprises in various business-to-business (B2B) sectors to build a bi-dimensional measurement scale of affective trust as a sentiment of security and affective attachment. For measurement scale development, established construction procedures were followed, including qualitative and quantitative surveys. The process can be summarized as: domain specification, generation of questionnaire items, empirical survey and iterative process of scale purification based on reliability assessment and validity checks. Findings: – The results indicate satisfactory psychometric properties of the new Affective Trust Scale (ATS). Furthermore, they demonstrate the scale's measurement invariance across business sectors. The research confirms the importance of affective aspects of trust and supports the reliability and validity of the measure. Nomological validity assessment of the scale shows that sentiment of security-based trust impacts investment in business relationships. Research limitations/implications: – The ATS developed and tested in the B2B French context needs to be evaluated taking into account several limitations. First, the specific context was a sample of buyers in France experiencing lasting relationships, suggesting that an extension of the study to other countries would be desirable. Also, the ATS needs to be further validated and confirmed in other contexts, for instance, within buyer–supplier relationship intensity. Practical implications: – The ATS can help firms to identify key parameters in buyer–seller relationships. It is important for the seller to collect information to determine the stage of the relationship before spending money on targeting customers, as they may not be ready to broaden the scope of their contract. The ATS can be very useful for companies to assess the state of the relationship and the strength of the bond in a timely manner and, therefore, anticipate the relational orientation. Segmentation based on relational phases requires tailoring to each form of trust strategies and hence the accurate identification of the relationship phase could help to better categorize and subcategorize customers with respect to the sentiment of security and affective attachment degrees. Furthermore, an understanding of the two dimensions is useful for key account managers to adjust relationship management toward specific actions (e.g. sentiment of security and/or affective attachment). The ATS could be very useful to guide managers in taking the right decision, by focusing both on sentiment of security and affective attachment dimensions of affective trust. Originality/value: – Affective trust is important to B2B managers, who frequently struggle to build and maintain close relationships with customers and suppliers. This paper adds insights into the complex but important construct of trust. The scale could be used for empirical studies of affective trust in B2B relationships. It may also help marketing managers develop better relationships with partners.